Solving problems: a statistical comparison of three root cause analysis tools - Doggett, Anthony Mark, author; Cobb, R. Brian, advisor; De Miranda, Michael A., advisor; Yohon, Teresa I., committee member; Folkestad, James E., committee member; Gloeckner, Gene, committee member (Colorado State University. Libraries, 2003)
The purpose of this quasi-experimental study was to compare the perceived differences between the cause-and-effect diagram (CED), the interrelationship diagram (ID), and the current reality tree (CRT) with regard to causality, factor relationships, usability, and participation. The independent variables were the CED, the ID, and CRT, which are graphical display tools designed for root cause analysis. The specific dependent variables were the perceived ability of each tool to identify causality and relationships between factors. In addition, the researcher was interested in the perceived usability of the tools and the perceived degree of participation. Using a within-subjects repeated measures design with counterbalancing, participants attempted to solve an organizational problem introduced via a scenario. Participants responded about their experience with each of the tools with regard to the dependent variables using a self-report instrument. Findings of the research indicated that participants could significantly distinguish differences between the tools with respect to usability, but could not perceive differences on causality, factor relationships, or participation. Other interesting findings included differences in process times, the types of questions asked, process observations, and generated tool outputs. The conclusions drawn from the experiment were that participants' perceptions of usability were driven primarily by the ease or difficulty of the tool use. The CED was perceived easiest to use while the CRT was the most difficult. The ID also emerged as an easy alternative for root cause analysis, but was not perceived differently in other aspects of usability. Another interesting result was that the quality of outputs varied greatly between the tools. Groups using the CED and ID were able to construct the tools with accuracy most of the time, but had difficulty finding specific and reasonable root causes. iii Reproduced with permission of the copyright owner. Further reproduction prohibited without permission. In comparison, the groups using the CRT were able to find specific and reasonable root causes over half the time regardless of construction accuracy. The implications for policy indicate that training, facilitation, and opportunities for group practice are important for all three tools. Varying degrees of training and expertise are required depending on the tool used, the complexity of the problem, and other group factors.
Keywords: industrial engineering; comparative analysis; problem solving; research; dictionaries; usability; identification; scientific method; causality; validity; perceptions; hypotheses; logic; decision making; variables; copyright; methods; literature reviews; variance analysis; dependent variables; within-subjects design